Contrafactual Counterpoint: Revisiting the Polyphonic Novel Metaphor with Faulkner's The Wild Palms1. - Delazari, Ivan (CounterText, 2019)
The article theorises the notion of contrapuntal polyphony as applied to literary narrative and sketches out an algorithm for reading William Faulkner's 1939 The Wild Palms in terms of the musical analogy. Contrapuntal fiction is contrafactual, since neither actual sound nor simultaneous parts of equal importance are presented in literary narrative. Such notions as 'the polyphonic novel' and 'novelistic counterpoint' are attacked from the vein of restrictionism by scholars who are dissatisfied with the metaphoricity of these terms despite their coiner Mikhail Bakhtin's disclaimer that no literal link to music is originally intended. Leaning on the heuristic and perceptual value of metaphors as illuminated by cognitive studies, this paper outlines an extensionist audionarratological alternative to the restrictionist approach by arguing that perceptual methods of processing parallel melodic lines and consecutive segments of narrative information share the common gestalt basis discussed in the auditory scene analysis of psychoacoustics. Opting to register and internalise certain details in the two apparently unrelated alternating stories of The Wild Palms, the reader begins to assemble a mental score and to learn performing the parts simultaneously, toward an integrated polyphonic whole.